Paper 66: Radiostereometric Analysis of Biceps Tenodesis: A Prospective Comparison of All-Suture Anchor vs. Interference Screw, Arthroscopic and Mini-Open Techniques. Issue 7 (30th July 2022) - Forlenza, Enrico; Okoroha, Kelechi; Williams, Brady; Patel, Harsh; Manderle, Brandon; Beletsky, Alexander; Chahla, Jorge; Yanke, Adam; Cole, Brian; Verma, Nikhil; Forsythe, Brian
Objectives: Recent studies suggest that similar results can be achieved via arthroscopic and open biceps tenodesis techniques. The purpose of this investigation was to quantify and compare the behavior of the biceps tenodesis construct in arthroscopic suprapectoral (ASPBT) and open subpectoral (OSPBT) techniques performed with either interference screw or suture anchor fixation, with radiostereometric analysis (RSA). Methods: A prospective cohort study was performed comparing migration of the biceps tendon after suprapectoral and subpectoral biceps tenodesis (BT) with Polyetheretherketone (PEEK) interference screw vs. all-suture suture anchor (ASSA) fixation. Patients with symptomatic biceps tendinopathy, anterior intertubercular groove tenderness, and positive biceps tension tests were included in the investigation. A tantalum bead, functioning as a radiostereometric marker, was sutured to the biceps tendon before final fixation of tendon tissue with either an interference screw or suture anchor. Following final fixation, AP radiographs were obtained intraoperatively. Follow up single view AP radiographs were obtained at one week and 3-months post-operatively. The distance from the center of the tantalum bead to the most proximal aspect of the humeral head was measured. Results: Of 128 patients enrolled, 120 (93.8%) were available for follow-up. The average age was 52.05±10.5 years, average BMI 30.8±5.4, and 29% of the patients were females. Groups were similar concerning patient demographics and concomitant procedures. At final follow up, there was no difference in distal migration between the OSPBT and ASPBT performed with an interference screw (4.31 vs. 4.02 mm, respectively, P=0.418). BT performed with a single ASSA demonstrated significantly more migration than BT performed with double ASSA (27.24 vs. 9.73 mm, respectively, P=0.005) and significantly more migration than the interference screw (27.24 26 vs. 4.31 mm, respectively, P<0.001). BT performed with the double ASSA technique demonstrated significantly more migration than the interference screw (9.73 vs. 4.02 mm, respectively, P=0.041). Three patients (11.1%) in the open single ASSA group, one patient in the arthroscopic double ASSA group (4.0%) suffered Popeye deformities. None of the patients in the interference screw cohorts experienced Popeye deformities. Conclusions: OSPBT and ASPBT demonstrate similar construct stability with use of interference screws as assessed by RSA. BT performed with single ASSA fixation resulted in more distal migration compared to double ASSA and interference screw fixation. Interference screw fixation provided more construct stability compared to a single and double ASSA, whether performed arthroscopically or with an open approach. These findings are the first in vivo results to characterize and quantify the biceps tenodesis construct in the post-operative period. Table 1. Patient Demographics and Other Characteristics. Table 2. Intraoperative Findings. Table 3. Tantalum bead migration at 1 week, 3 months and between 1 week and 3 months for arthroscopic and open techniques. Figure 1. Comparison of postoperative construct migration for the four studied techniques of biceps tenodesis measured by radiostereometric analysis.